A efetividade de escovas descartáveis e submetidas à desinfecção para a higiene bucal em pacientes ventilados mecanicamente: ensaio clínico - Gonçalves, Fernanda Alves Ferreira (2019)
INTRODUCTION: Invasive ventilatory and intubated patients are dependent on the nursing team. The mechanical removal of the biofilm with toothbrush is the first option, but after single use it can be contaminated by microorganisms from the oral cavity, as well as from the external environment. The use of the brush should be associated with chemical control of chlorhexidine digluconate, which is semi-critical and requires high level disinfection or be discarded. Peracetic acid is a high-level disinfectant, but has not been tested for use on toothbrushes. AIM: To compare the effectiveness of the use of disposable toothbrushes and disinfection with peracetic acid used for oral hygiene (OH) of patients under mechanical ventilation. MATERIALS AND METHODS: Randomized-controlled clinical trial performed at an intensive care unit of a public hospital in Goiânia / GO. Data were collected from 31 patients, intubated and under mechanical ventilation, between June 2017 and August 2018. The patients were divided into Control Group (OH with disinfected brushes) and Intervention Group (HB with brushes discarded). A dental evaluation was performed on day 1. Saliva collection was performed on day 1, day 3 and day 5 for counting of colony forming units (CFU). HB was performed twice a day, for up to five days, with 0.12% CHX gel and disinfected or discarded brushes. RESULTS: At admission, patients presented poor oral hygiene, periodontal disease, periodontitis and gingivitis. Most of the participants were male, with a mean age of 59.0 ± 14.4 years and mean of 19 teeth. Throughout the days of HB there was a decreasing tendency of buccal and lingual biofilms, however, there was no significant reduction of UFC, with no difference between the groups that used disposable brushes and disinfected brushes. In relation to the bacteria isolated on the fifth day, there was homogeneity in both groups, with predominance of Pseudomonas aeruginosa, Enterococcus faecium, Klebsiella pneumoniae and Staphylococcus haemolyticus. CONCLUSIONS: There was no difference in tooth and tongue brushing, performed with single use brushes, discarded or disinfected at each use. The important thing is to brush properly, following established protocols.